2021
DOI: 10.17066/tpdrd.1001724
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Resilience and Life Satisfaction of Healthcare Professionals in Turkey: The Mediating Role of Fear of COVID

Abstract: COVID-19 pandemic has caused devastating consequences as psychological traumas especially for healthcare professionals, who play an active role and are at greatest risk in this process. It is important to protect their health to prevent the health system from collapsing. The purpose of this study is to reveal the mediating role of coronavirus fear in the effect of psychological resilience on life satisfaction. coronavirus fear, psychological resilience, and life satisfaction scales were applied to 414 healthca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
2
0
1
Order By: Relevance
“…Similarly, many research findings (Giorgio et al, 2020;Jue & Ha, 2022;Özmen et al, 2021;Rasskazova et al, 2020) showing that fear of Covid-19 negatively affects SWB are available. Again, in parallel with this finding, there are also studies (Karagöz et al, 2021;Satıcı et al, 2021) reporting that fear of Covid-19 reduced life satisfaction.…”
Section: Limitationsmentioning
confidence: 53%
“…Similarly, many research findings (Giorgio et al, 2020;Jue & Ha, 2022;Özmen et al, 2021;Rasskazova et al, 2020) showing that fear of Covid-19 negatively affects SWB are available. Again, in parallel with this finding, there are also studies (Karagöz et al, 2021;Satıcı et al, 2021) reporting that fear of Covid-19 reduced life satisfaction.…”
Section: Limitationsmentioning
confidence: 53%
“…They reported that resilience mediated the effect of COVID-19 fear on depression, anxiety, and stress among healthcare professionals. Karagöz et al [36] reported that increased COVID-19 fear decreased psychological resilience and life satisfaction among Turkish healthcare professionals. Frequent exposure to COVID-19 cases and deaths may probably aggravate fear and increase vulnerability to burnout and erode coping resources.…”
Section: Differential Vulnerability To Psychological Distressmentioning
confidence: 99%
“…Koronavirus 2019 hastalığı (Coronavirus disease 2019, COVID-19) salgını 11 Mart 2020 tarihi itibariyle Dünya Sağlık Örgütü tarafından pandemi olarak ilan edilmiştir [1]. COVID-19 pandemisinin; eğitime etkileri [2], psikolojik etkileri [3], işletmelerdeki dijital dönüşüme etkileri [4], çalışma hayatına etkileri [5], vücuttaki bazı organlara muhtemel zararları [6]…”
Section: Introductionunclassified